Research on forming quality of poly-wedge pulley spinning - Xiu-quan, Cheng; Qin-xiang, Xia; Jia-zi, Wang; Dong-he, Li (Cranfield University Press, 2013)
As an important power transmission part, pulleys are widely used in automobile industry, agricultural machinery, pumps and machines. A near-net forming process for six-wedge belt pulleys manufacturing was put forward. For this purpose, the required tooth shape and size can be formed directly by spinning without machining. The whole manufacturing procedures include blanking, drawing and spinning. The spinning procedure includes five processes, performing, drumming, thickening, toothing and finishing. The forming defects occurred during each forming processes of poly-wedge pulley spinning, such as the drumming failure, flanged opening-end, folded side-wall, insufficient bottom size, flashed opening-end, cutting-off bottom, are introduced, and the factors influencing the defects are analyzed. The corresponding preventive measures are put forward.
Keywords: spinning; poly-wedge pulley; forming quality